A review on unit operations, challenges, opportunities, and strategies to improve algal based biodiesel and biorefinery - Kumar, Lakhan; Mohan, Lalit; Anand, Raksha; Joshi, Vandana; Chugh, Mohita; Bharadvaja, Navneeta (Frontiers in Chemical Engineering, 2022)
Globally, the demand for energy is increasing with an emphasis on green fuels for a sustainable future. As the urge for alternative fuels is accelerating, microalgae have emerged as a promising source that can not only produce high lipids but many other platform chemicals. Moreover, it is a better alternative in comparison to conventional feedstock due to yearlong easy and mass cultivation, carbon fixation, and value-added product extraction. To date, numerous studies have been done to elucidate these organisms for large-scale fuel production. However, enhancing the lipid synthesis rate and reducing the production cost still remains a major bottleneck for its economic viability. Therefore, this study compiles information on algae-based biodiesel production with an emphasis on its unit operations from strain selection to biofuel production. Additionally, strategies to enhance lipid accumulation by incorporating genetic, and metabolic engineering and the use of leftover biomass for harnessing bio-products have been discussed. Besides, implementing a biorefinery for extracting oil followed by utilizing leftover biomass to generate value-added products such as nanoparticles, biofertilizers, biochar, and biopharmaceuticals has also been discussed.